Aqueous gel
A biodegradable aqueous gel with high water content and compressive strength is achieved using a crosslinked polyamide from bio-derived itaconic acid and diamine, addressing environmental concerns associated with petroleum-based materials.
Patent Information
- Application Number
- JP2023176174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-23
AI Technical Summary
Existing aqueous gels face challenges in achieving high water content while maintaining compressive strength, and they typically rely on petroleum-derived materials, which are environmentally harmful.
Development of a biodegradable aqueous gel using a crosslinked polyamide derived from bio-derived itaconic acid and diamine, which is produced without petroleum-based materials, and has a water content of 50-70% and compressive strength enhanced by crosslinking.
The resulting aqueous gel exhibits high water content and compressive strength, is biodegradable, and environmentally friendly, making it suitable for various applications without contributing to plastic pollution.
Smart Images

Figure 2025066511000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous gel. More specifically, the present invention relates to an aqueous gel that can be prepared using a bio-derived compound as a raw material and is environmentally friendly, a method for producing the same, and a crosslinked polymer that can be suitably used as a raw material for the aqueous gel and a method for producing the same. [Background technology]
[0002] Plastics are widely used in various fields because they are lightweight and easy to mold. Petroleum is generally used as the raw material for plastics. The production volume of plastics that use petroleum as the raw material is estimated to be just under 400 million tons worldwide in 2020.
[0003] However, plastics, which use petroleum as a raw material, are considered to be one of the causes of environmental pollution. More specifically, not only does it consume a huge amount of energy to produce plastic from petroleum and emit carbon dioxide gas, which is considered a greenhouse gas, but it also causes soil pollution from discarded plastic and air pollution from the incineration of discarded plastic. Therefore, reliance on petroleum as a raw material for plastics is a factor that hinders the Sustainable Development Goals (SDGs) adopted by the United Nations General Assembly in 2015.
[0004] It has also been pointed out that approximately 150 million tons of plastic waste will have accumulated in the ocean as of 2023. Since plastic waste becomes microplastics in the ocean, it is estimated that approximately 50% of marine life, including sea turtles, and approximately 90% of seabirds, have ingested plastic waste such as microplastics. There are concerns that marine life may mistakenly ingest plastic waste, and that humans may ingest marine life that has mistakenly ingested the plastic waste, which could have adverse effects on the human body. There are also concerns that the lives of marine life may be threatened if marine life ingests microplastics or becomes entangled in plastic fishing lines.
[0005] Under these circumstances, the development of plastics that do not use petroleum as a raw material and biodegradable plastics is being considered. The development of aqueous gels that do not use petroleum as a raw material and are biodegradable is also being considered.
[0006] Conventionally, aqueous gels have been used in a wide range of fields. For example, in the field of cosmetics, an aqueous gel containing a high molecular weight silicone compound, a low molecular weight silicone compound, a crosslinked carboxyvinyl polymer, an alkali compound, and an alkylene oxide adduct of alcohols has been proposed, and the aqueous gel is used in hair styling products (see, for example, Patent Document 1). In addition, as another aqueous gel, an aqueous gel consisting of an aqueous solution of an anionic water-soluble polymer compound such as poly(meth)acrylic acid or its alkali metal salt, or a hydrolyzate of a methyl vinyl ether-maleic anhydride copolymer, a crosslinker, and microfibrous cellulose has been proposed, and the aqueous gel is used in fragrances (see, for example, Patent Document 2). All of these aqueous gels are made of petroleum-derived plastics (polymers) as raw materials. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 4-356410 [Patent Document 2] JP 2003-277637 A Summary of the Invention [Problem to be solved by the invention]
[0008] One of the technical challenges in aqueous gels is the improvement of their water content. However, as increasing the water content of an aqueous gel results in a relative decrease in the compressive strength of the aqueous gel, there is a demand for the development of aqueous gels that have both high water content and high compressive strength.
[0009] Furthermore, as mentioned above, in recent years, from the viewpoint of protecting the global environment, there has been a demand for the development of biodegradable aqueous gels that can be produced without using petroleum as a raw material.
[0010] The present invention has been made in consideration of the above-mentioned conventional techniques, and an object of the present invention is to provide an aqueous gel which has both high water content and high compressive strength, can be produced without using petroleum as a raw material, and is biodegradable, and a method for producing the same, as well as a crosslinked polymer which can be suitably used in the aqueous gel and a method for producing the same. [Means for solving the problem]
[0011] The present invention relates to (1) Formula (I):
[0012] [ka]
[0013] (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. A crosslinked polyamide having a crosslinked structure represented by (2) Crosslink density is 0.5 to 6 mg / cm 3 The crosslinked polyamide according to (1), (3) Itaconic acid or a salt thereof and a compound represented by the formula (II): H2N-R 1 -NH2(II) (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. and a diamine represented by the formula: (4) Itaconic acid or a salt thereof and a compound represented by the formula (II): H2N-R 1 -NH2(II) (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. and heating the itaconate diamine to 200 to 250°C. (5) An aqueous gel comprising a crosslinked polyamide and water, the crosslinked polyamide being represented by the formula (I):
[0014] [ka]
[0015] (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. and an aqueous gel comprising the crosslinked polyamide having a crosslinked structure represented by the formula: (6) The aqueous gel according to (5) above, having a water content of 50 to 70% by mass; and (7) A method for producing an aqueous gel, comprising impregnating the crosslinked polyamide obtained in (3) or (4) above with water. Regarding. Effect of the Invention
[0016] According to the present invention, there are provided an aqueous gel which has both high water content and high compressive strength, can be produced without using petroleum as a raw material, and has biodegradability, a method for producing the same, and a crosslinked polymer which can be suitably used in the aqueous gel, and a method for producing the same. [Brief description of the drawings]
[0017] [Figure 1] 1 is a graph showing the 1H-NMR spectrum of the itaconate diamine obtained in Preparation Example 1. [Diagram 2] 1 is a graph showing the 1H-NMR spectrum of Polyamide I obtained in Production Example 9. [Diagram 3] 1 is a graph showing XPS spectra of Polyamide I obtained in Production Example 9 and Crosslinked Polyamide R obtained in Example 8. [Figure 4] 1 is a graph showing infrared absorption spectra of polyamide I obtained in Production Example 9, and crosslinked polyamides A to E and crosslinked polyamides P to R obtained in Examples 1 to 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The crosslinked polyamide of the present invention is prepared by using a polyamide as a raw material. Itaconic acid (salt) and a diamine are used as raw materials for the polyamide.
[0019] (1) Itaconic acid (salt) The term "itaconic acid (salt)" refers to itaconic acid or an itaconate salt. Itaconic acid and an itaconate salt may be used alone or in combination.
[0020] Itaconic acid has one highly reactive vinylidene group and two carboxy groups. Itaconic acid is listed as one of the key biorefinery substances specified by the U.S. Department of Energy (DOE). Itaconic acid can be produced in large quantities at low cost by fermenting grains such as corn using fungi such as Aspergillus terreus without using petroleum as a raw material. Bio-derived itaconic acid produced using the fungi is excellent in terms of protecting the global environment, and can be suitably used in the present invention. Bio-derived itaconic acid produced using the fungi can be easily obtained commercially from, for example, Iwata Chemical Industry Co., Ltd., Cargill, etc.
[0021] Itaconates can be easily prepared by neutralizing itaconic acid with an alkali such as sodium hydroxide. Examples of itaconates include alkali metal itaconates such as sodium itaconate and potassium itaconate, and ammonium itaconate, but the present invention is not limited to these examples. Among itaconates, alkali metal itaconates are preferred, and sodium itaconate is more preferred.
[0022] (2) Diamine As the diamine, a compound of the formula (II): H2N-R 1 -NH2(II) (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. It is possible to use a diamine represented by the following formula:
[0023] In formula (II), R 1is a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. Examples of the substituent include an alkoxy group having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, or a butoxy group; a hydroxyl group; a halogen atom, such as a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom; a cyano group; and a nitrile group, but the present invention is not limited to these examples. Among the substituents, an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, and a halogen atom are preferred.
[0024] Examples of diamines represented by formula (II) include hydrazine, 1,2-ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, etc., but the present invention is not limited to these examples. These diamines may be used alone or in combination of two or more kinds.
[0025] The diamine is preferably an alkylene diamine having 2 to 5 carbon atoms in the alkylene group from the viewpoint of obtaining an aqueous gel having appropriate water resistance, decomposability in water, and durability. Among the diamines, diamines produced using bacteria (so-called bio-derived diamines) are preferred from the viewpoint of protecting the global environment. Examples of bio-derived diamines include 1,5-pentanediamine, but the present invention is not limited to these examples. 1,5-pentanediamine (1,5-diaminopentane) is called cadaverine. Cadaverine is found in a small number of microorganisms. Cadaverine is also a compound produced by hydrolysis of proteins when animal body tissues decay. Cadaverine can be biosynthesized from L-lysine by L-lysine decarboxylase in Escherichia coli (Gram-negative bacterium) (see, for example, QIAN et al., "Metabolic engineering of Escherichia coli for the production of cadaverine: A five carbon diamine", BIOTECHNOLOGY BIOENGINEERING, Vol. 108, 2011, pp. 93-103).
[0026] When cadaverine is used as the diamine, a polyamide synthesized using the cadaverine and itaconic acid (salt) has high tensile strength and excellent water absorption properties, and an aqueous gel using the polyamide has a high water content and high compressive strength, and is therefore expected to be used as a functional gel.
[0027] (3) Itaconic acid diamine Itaconic acid diamine can be used as a raw material for polyamide. Itaconic acid diamine can be obtained by reacting itaconic acid (salt) with a diamine.
[0028] In the present invention, itaconic acid (salt) and diamine can both be bio-derived compounds. The itaconic acid diamine obtained by polymerizing bio-derived itaconic acid or its salt with bio-derived diamine can be called bio-derived itaconic acid diamine because a bio-derived compound is used as a raw material.
[0029] Since itaconic acid (salt) and diamine react in stoichiometric amounts, the amount of diamine per mole of itaconic acid (salt) is theoretically 1 mole. However, the amount of itaconic acid (salt) may be in excess of the amount of diamine, or the amount of diamine may be in excess of the amount of itaconic acid (salt). The amount of diamine per mole of itaconic acid (salt) is usually preferably 0.9 to 1.1 moles.
[0030] When itaconic acid (salt) and diamine are reacted with each other, the itaconic acid (salt) and the diamine are dissolved in a solvent.
[0031] The solvent is preferably a solvent capable of sufficiently dissolving itaconic acid (salt) and diamine. Among the solvents, aqueous solvents are preferred. Examples of aqueous solvents include water and organic solvents capable of sufficiently dissolving itaconic acid (salt) and diamine.
[0032] The water may be any of city water, distilled water, purified water, and pure water, but distilled water, purified water, and pure water are preferred. Examples of organic solvents capable of sufficiently dissolving itaconic acid (salt) and diamine include hydrophilic organic solvents. Examples of the hydrophilic organic solvents include monohydric alcohols such as methanol, ethanol, isopropyl alcohol, n-propyl alcohol, and allyl alcohol; polyhydric alcohols such as ethylene glycol, propylene glycol, butane polyol, pentane polyol, hexane polyol, heptane polyol, and dipropylene glycol; ketones such as acetone, methyl ethyl ketone, and methyl propyl ketone; aliphatic organic acid alkyl esters such as methyl formate, ethyl formate, methyl acetate, and methyl acetoacetate; and alkyl ethers of polyhydric alcohols such as diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and dipropylene glycol monomethyl ether, but the present invention is not limited to these examples. These hydrophilic organic solvents may be used alone or in combination of two or more. Among these organic solvents, monohydric alcohols having 1 to 4 carbon atoms are preferred.
[0033] There is no particular limitation on the temperature of the solvent when itaconic acid (salt) and diamine are dissolved in the solvent, the reaction temperature of itaconic acid (salt) and diamine, the atmosphere when itaconic acid (salt) and diamine are dissolved in the solvent, and the atmosphere when itaconic acid (salt) and diamine are reacted. The temperature of the solvent when itaconic acid (salt) and diamine are dissolved in the solvent, and the reaction temperature of itaconic acid (salt) and diamine are usually room temperature. The atmosphere when itaconic acid (salt) and diamine are dissolved in the solvent, and the atmosphere when itaconic acid (salt) and diamine are reacted may be air or an inert gas such as nitrogen gas or argon gas. In order to avoid the influence of oxygen gas contained in the air, the atmosphere is preferably an inert gas.
[0034] Although a mixture of itaconic acid (salt) and diamine may be dissolved in a solvent, it is preferable to mix a solution of itaconic acid (salt) with a solution of diamine from the viewpoint of uniformly dissolving itaconic acid (salt) and diamine. The amount of solvent per 100 parts by mass of itaconic acid (salt) and the amount of solvent per 100 parts by mass of diamine are preferably about 10 to 30 parts by mass, respectively, from the viewpoint of promoting the reaction between itaconic acid and diamine.
[0035] The reaction time between itaconic acid (salt) and diamine cannot be determined in general because it depends on the reaction temperature between itaconic acid (salt) and diamine. The reaction time between itaconic acid (salt) and diamine can be the time required for sufficient production of itaconic acid diamine. The reaction time between itaconic acid (salt) and diamine is usually about 8 to 16 hours. The production of itaconic acid diamine can be confirmed by nuclear magnetic resonance (NMR).
[0036] By reacting itaconic acid (salt) with a diamine in the above manner, a compound represented by the formula (III):
[0037] [ka]
[0038] (In the formula, R 1 is the same as above) A reaction mixture containing itaconate diamine represented by the formula (I) can be obtained. The itaconate diamine obtained above can be recovered by filtering the reaction mixture. The recovered itaconate diamine may be used as it is, or may be used after purification. In addition, the itaconate diamine may be used after drying as necessary.
[0039] The itaconate diamine obtained above can be used as a raw material for polyamides, and can also be used as a raw material for crosslinked polyamides.
[0040] (4) Polyamide In the present invention, the itaconate diamine is used as a raw material for polyamide. The itaconate diamine can be polymerized to obtain polyamide. When a bio-derived itaconate diamine is used as the itaconate diamine, the obtained polyamide can be called bio-nylon, since a bio-derived compound is used as a raw material.
[0041] Polyamides using the above-mentioned itaconate diamine as a raw material have higher heat resistance than general nylons and similar mechanical properties.
[0042] The polyamide is irradiated with ultraviolet light having a wavelength of 250 to 450 nm as artificial sunlight using, for example, a high-pressure mercury lamp in the presence of water, to obtain a compound represented by the formula:
[0043] [ka]
[0044] (In the formula, R 1 is the same as above. m is a positive integer indicating the degree of polymerization. It has been reported that the pyrrolidone ring of the polyamide opens, dissolves in water, and is decomposed by microorganisms such as bacteria contained in the soil when buried in soil (for example, KANEKO et al., “Syntheses of High-Performance Biopolyamides Derived from Itaconic Acid and Their Environmental Corrosion”, Macromolecules, 2023, No. 46, pp. 3719-3725, etc.). In addition, the low toxicity of solutions containing dissolved polyamides has been confirmed by the marine luminescent bacteria luminescence inhibition test [ISO 11348-1 (2007)] Aliivibrio fisheri, 30 min-EC50, marine microalgae growth inhibition test [ISO 10253 (2016)] Phaeodactylum tricornutum (diatom), 3-day EC50, NOEC, and saltwater crustacean acute lethality test [ISO / TS 20787 (2017)] Artemia salina, 2 day-LC5.
[0045] Therefore, even if the polyamide is discharged into the ocean, it will become water-soluble due to the ultraviolet rays contained in sunlight, dissolve in seawater, and be decomposed by microorganisms such as bacteria contained in the soil, making it biodegradable.Furthermore, since the solution in which the polyamide is dissolved has low toxicity, it can be suitably used as a biodegradable polyamide (biodegradable polymer) that decomposes in the natural environment.
[0046] The polyamide can be obtained by polymerizing the itaconate diamine. More specifically, the polyamide can be, for example, a polyamide represented by the formula (IV):
[0047] [ka]
[0048] (In the formula, R 1 is the same as above. n is a positive integer indicating the degree of polymerization. It can be obtained by heating and polymerizing itaconate diamine as shown in the formula:
[0049] The heating temperature of the itaconate diamine when the itaconate diamine is heated to polymerize it is preferably 150 to 190° C., more preferably 155 to 190° C., and even more preferably 160 to 190° C., from the viewpoint of efficiently obtaining a polyamide. The heating temperature may be constant or may be increased stepwise.
[0050] The heating time when the itaconate diamine is heated and polymerized is the time required for polyamide to be produced. The heating time of the itaconate diamine varies depending on the heating temperature and the like, so cannot be generally determined, but is usually about 3 to 15 hours. The atmosphere when the itaconate diamine is polymerized is not particularly limited, and may be air or an inert gas such as nitrogen gas or argon gas, but is preferably an inert gas from the viewpoint of avoiding the influence of oxygen gas contained in air.
[0051] When itaconate diamine is polymerized, it is preferable to add a suitable amount of catalyst to itaconate diamine from the viewpoint of efficiently preparing polyamide. Examples of the catalyst include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and trilithium phosphate, but the present invention is not limited to these examples. Among the catalysts, sodium dihydrogen phosphate is preferable.
[0052] By heating and polymerizing itaconic acid diamine as described above, a compound represented by the formula (V):
[0053] [ka]
[0054] It is possible to obtain a polyamide having a repeating unit represented by the following formula: The polyamide obtained above is usually allowed to cool to room temperature.
[0055] The polyamide is obtained by homopolymerizing itaconate diamine, and is therefore usually a homopolymer made of itaconate diamine. However, the polyamide may contain repeating units other than the repeating units derived from itaconate diamine by polymerizing itaconate diamine with other compounds within the scope of the present invention.
[0056] The number average molecular weight of the polyamide is not particularly limited, but from the viewpoint of obtaining a crosslinked polyamide having an appropriate swelling rate with water and water content and having good mechanical properties such as compressive elastic modulus, it is preferably 2000 to 100000, and more preferably 2500 to 50000. The number average molecular weight of the polyamide is a value measured based on the method described in the following examples.
[0057] The polyamide obtained above may be used as it is, or may be purified by washing with a poor solvent such as methanol, if necessary. The polyamide may also be used after drying, if necessary.
[0058] (5) Crosslinked polyamide In the present invention, the crosslinked polyamide means a polyamide having a crosslinked structure. Methods for producing a crosslinked polymer include (A) a method for producing a crosslinked polyamide by crosslinking the polyamide, and (B) a method for producing a crosslinked polyamide by polymerizing and crosslinking the itaconate diamine.
[0059] (A) A method for producing a crosslinked polyamide by crosslinking a polyamide In the method for producing a crosslinked polyamide by crosslinking a polyamide, the crosslinked polyamide can be obtained by heating the polyamide.
[0060] The heating temperature of the polyamide is 200 to 250°C, preferably 205 to 245°C, and more preferably 210 to 240°C, from the viewpoints of efficiently crosslinking the polyamide and preventing the polyamide from being denatured.
[0061] The atmosphere in which the polyamide is heated is preferably an inert gas such as nitrogen gas or argon gas, in order to avoid the effects of oxygen gas contained in the air.
[0062] The heating time of polyamide varies depending on the heating temperature of the polyamide, so it cannot be determined in general, and it is preferable to adjust it appropriately according to the heating temperature of the polyamide. In general, as the heating time of polyamide increases, the crosslinking of the polyamide progresses, the crosslinking density increases, and the swelling rate and water content tend to decrease. For this reason, it is preferable to adjust the heating time of polyamide according to the desired properties of the crosslinked polyamide to be produced. As an example of the heating time of polyamide, the heating time of polyamide depends on the heating temperature of polyamide, but from the viewpoint of sufficiently improving the crosslinking density, it is preferably 3 hours or more, more preferably 4 hours or more, and even more preferably 5 hours or more, and from the viewpoint of improving the swelling rate and water content, it is preferably 80 hours or less, more preferably 75 hours or less.
[0063] By heating the polyamide as described above, a compound represented by the formula (I):
[0064] [ka]
[0065] (In the formula, R 1 is the same as above) It is possible to obtain a crosslinked polyamide having a crosslinked structure represented by the following formula:
[0066] (B) A method for producing a crosslinked polyamide by polymerizing and crosslinking itaconate diamine In the method for producing a crosslinked polyamide by polymerizing and crosslinking itaconated diamine, the crosslinked polyamide can be obtained by heating the itaconated diamine.
[0067] The heating temperature of the itaconated diamine is 200 to 250° C., preferably 205 to 245° C., and more preferably 210 to 240° C., from the viewpoints of efficiently polymerizing and crosslinking the itaconated diamine and suppressing denaturation of the resulting crosslinked polyamide.
[0068] The atmosphere in which itaconate diamine is heated is preferably an inert gas such as nitrogen gas or argon gas, from the viewpoint of avoiding the influence of oxygen gas contained in the air.
[0069] The heating time of itaconate diamine varies depending on the heating temperature of itaconate diamine, so it cannot be determined in general, and it is preferable to adjust it appropriately according to the heating temperature of itaconate diamine. In general, as the heating time of itaconate diamine increases, the crosslinking reaction proceeds in parallel with the polymerization reaction of itaconate diamine, increasing the crosslinking density, and the swelling rate and water content of the crosslinked polyamide obtained tend to decrease. For this reason, it is preferable to adjust the heating time of itaconate diamine according to the desired properties of the crosslinked polyamide produced. As an example of the heating time of itaconate diamine, the heating time of itaconate diamine depends on the heating temperature of itaconate diamine, but from the viewpoint of sufficiently improving the crosslinking density, it is preferably 3 hours or more, more preferably 4 hours or more, and even more preferably 5 hours or more, and from the viewpoint of improving the swelling rate and water content, it is preferably 40 hours or less, more preferably 30 hours or less.
[0070] As described above, itaconate diamine is heated to polymerize and crosslink the itaconate diamine, thereby obtaining a crosslinked polyamide. The crosslinked polyamide thus obtained has a crosslinked structure represented by formula (I), similar to the method of producing a crosslinked polyamide by heating the polyamide to crosslink it.
[0071] The crosslink density of crosslinked polyamides varies depending on the manufacturing method. Crosslinked polyamides usually have a crosslink density of 0.5 to 6 mg / cm 3 The crosslink density of the crosslinked polyamide is a value determined based on the method described in the following examples.
[0072] The fact that the crosslinked polyamide has the crosslinked structure represented by formula (I) can be confirmed by Fourier transform infrared spectroscopy (FT-IR) and solid-state nuclear magnetic resonance ( 13 It can be analyzed by NMR (C-NMR), X-ray photoelectron spectroscopy (XPS), etc.
[0073] (6) Aqueous gel The aqueous gel of the present invention can be easily prepared by impregnating a crosslinked polyamide with water. Examples of methods for impregnating a crosslinked polyamide with water include a method of immersing the crosslinked polyamide in water, but the present invention is not limited to such a method.
[0074] Examples of water used when impregnating the crosslinked polyamide include city water, distilled water, purified water, and pure water, but the present invention is not limited to these examples. The type of water can be appropriately selected depending on the application of the crosslinked polyamide. Among the water, distilled water, purified water, and pure water are preferred. The water may contain an aqueous organic solvent such as a lower alcohol, as long as the object of the present invention is not hindered.
[0075] The aqueous gel of the present invention may contain an appropriate amount of additives depending on the application, if necessary. Examples of additives include colorants such as pigments and dyes, ultraviolet absorbers, ultraviolet stabilizers, antioxidants, rust inhibitors, antibacterial agents, plasticizers, algae inhibitors, fungicides, flame retardants, and foaming agents, but the present invention is not limited to these examples. These additives may be used alone, or two or more types may be used in combination. The amount of additives varies depending on the type of additive, so it cannot be determined in general, and it is preferable to determine the amount appropriately depending on the type of additive.
[0076] Examples of methods for incorporating an additive into an aqueous gel include a method of adding an additive to a polyamide, crosslinking the polyamide to produce a crosslinked polyamide, incorporating the additive into the crosslinked polyamide, and impregnating the crosslinked polyamide containing the additive with water to obtain an aqueous gel; a method of adding an additive to itaconate diamine, polymerizing and crosslinking the itaconate diamine to incorporate the additive into the crosslinked polyamide, and impregnating the crosslinked polyamide containing the additive with water to obtain an aqueous gel; and a method of impregnating the crosslinked polyamide with water containing the additive to obtain an aqueous gel; however, the present invention is not limited to these methods.
[0077] The temperature of the water when the crosslinked polyamide is impregnated with water is not particularly limited, but is preferably 5 to 85° C., more preferably 10 to 80° C., and even more preferably room temperature.
[0078] The time required for impregnating the crosslinked polyamide with water varies depending on the swelling rate of the resulting aqueous gel with water, the water content, the compressive elastic modulus, the crosslinking density, etc., and is preferably adjusted appropriately depending on these properties.
[0079] By hydrating (impregnating) the crosslinked polyamide in the manner described above, an aqueous gel can be obtained.
[0080] The aqueous gel of the present invention has the advantage of being environmentally friendly, since it can be produced without using organic compounds such as petroleum-derived monomers and polymerization initiators that have been conventionally used in the production of aqueous gels.
[0081] (7) Properties of aqueous gels According to the present invention, by appropriately adjusting the heating temperature and heating time when crosslinking the polyamide or itaconate diamine by heating, it is possible to obtain a crosslinked polyamide having the desired water swelling ratio, water content, compressive elastic modulus and crosslink density.
[0082] (A) Aqueous gel containing crosslinked polyamide obtained by crosslinking polyamide The crosslinking density of the crosslinked polyamide contained in the aqueous gel is 0.5 to 5 mg / cm 3 The crosslink density of the crosslinked polyamide is a value determined based on the method described in the following examples.
[0083] The swelling ratio of the aqueous gel in water is in the range of 200 to 300%, particularly 215 to 295%, the water content is in the range of 50 to 70 mass%, and the compressive modulus is in the range of 5 to 70 kPa, particularly 8 to 70 kPa. The swelling ratio of the aqueous gel in water, the water content, and the compressive modulus are all values determined according to the method described below.
[0084] (B) Aqueous gel containing a crosslinked polyamide obtained by polymerizing and crosslinking itaconate diamine The crosslinking density of the crosslinked polyamide contained in the aqueous gel is 5 to 6 mg / cm 3 , especially 5.5~5.8mg / cm 3 The crosslink density of the crosslinked polyamide is a value determined based on the method described in the following examples.
[0085] The swelling rate of the aqueous gel with water is in the range of 200 to 300%, particularly 250 to 260%, the water content is in the range of 50 to 70% by mass, particularly 60 to 65% by mass, and the compressive elastic modulus is in the range of 90 to 100 kPa, particularly 95 to 100 kPa. The swelling rate of the aqueous gel with water, the water content, and the compressive elastic modulus are all values determined according to the method described below.
[0086] From the above, the aqueous gel of the present invention has the advantage of having a high swelling rate and water content in water. In addition, the aqueous gel containing the crosslinked polyamide obtained by polymerizing and crosslinking itaconate diamine has a swelling rate and water content that are not significantly different from those of the aqueous gel containing the crosslinked polyamide obtained by crosslinking polyamide, but has a relatively high crosslink density and is therefore superior in compressive elastic modulus.
[0087] The aqueous gel of the present invention has a high swelling rate and water content in water, and the compressive modulus can be adjusted over a wide range by changing the production method, and therefore can be used in a variety of applications as an alternative aqueous gel to conventional aqueous gels.
[0088] The aqueous gel of the present invention can be used as an aqueous gel in normal conditions, and the pyrrolidone ring contained in the crosslinked structure of the aqueous gel is opened by ultraviolet light contained in sunlight, etc., as described above, to become water-soluble, and since the amide bond is hydrolyzable, the crosslinked structure of the aqueous gel is cleaved to reduce the molecular weight, so that conventional microplastics do not accumulate in the body, and even if they are orally ingested, they are easily excreted from the body, and the polyamide constituting the aqueous gel is safe in the body as described above. In addition, when the aqueous gel or its decomposition products are precipitated at the bottom of, for example, the ocean, rivers, lakes, etc., they are decomposed by microorganisms such as bacteria contained in the mud at the bottom.
[0089] Therefore, the aqueous gel of the present invention has the degradability of being dissolved in water by hydrolysis, and is biodegradable and unlikely to cause adverse effects even if introduced into the body, so it can be said to be an aqueous gel that is friendly to the global environment.
[0090] (8) Uses of aqueous gel The shape of the aqueous gel of the present invention is arbitrary and can be appropriately adjusted depending on the application of the aqueous gel. The aqueous gel may be in the form of a film, a sheet, a columnar, a cylindrical, a spherical, or a polygonal shape. The aqueous gel may be molded into a predetermined shape using a mold. The aqueous gel may be molded into a sheet, and used in the form of a laminate in which a reinforcing material such as a woven fabric, a nonwoven fabric, a resin sheet, or a resin film is provided on one surface of the sheet-like aqueous gel.
[0091] As described above, the aqueous gel of the present invention has a high swelling rate and water content in water, and has a wide range of compressive elasticity, and is therefore expected to be used in a wide range of fields, such as new artificial baits to replace artificial baits such as silicone rubber worms, cell culture sheets, contact lenses, cosmetic packs, drug delivery materials for administering drugs into the body, artificial cartilage, artificial skin, artificial breasts, base materials for fragrances, electrolytes for lithium ion secondary batteries, vibration-proofing materials, and coating agents for various components that require hydrophilicity. EXAMPLES
[0092] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0093] Itaconic acid and cadaverine (1,5-pentanediamine) used in each example were obtained from Tokyo Chemical Industry Co., Ltd. and used as received. Ethanol, dimethyl sulfoxide (DMSO) and sodium dihydrogen phosphate were obtained from Kanto Chemical Co., Ltd. and used as received.
[0094] The physical properties of the itaconate diamine, polyamide, crosslinked polyamide and aqueous gel were examined by the following methods.
[0095] [Nuclear magnetic resonance ( 1 H-NMR, 13 C-NMR) Nuclear magnetic resonance ( 1 H-NMR, 13 For C-NMR, a nuclear magnetic resonance spectrometer (manufactured by Bruker, trade name: AVANCE 400, 400 MHz) was used. 5 mg of sample was dissolved in 0.5 mL of dimethyl sulfoxide (DMSO-d6) (manufactured by Kanto Chemical Industry Co., Ltd.), the resulting solution was placed in a glass sample tube, and measurements were taken at 25°C with 16 accumulations.
[0096] [Fourier transform infrared spectroscopy (FT-IR)] Fourier transform infrared spectroscopy (FT-IR) was performed using a Fourier transform infrared spectrometer (Perkin Elmer, product name: Spectrum 100, ATR method) in the measurement wave number range of 400 to 4000 cm -1 The measurement was performed 32 times.
[0097] [X-ray photoelectron spectroscopy (XPS)] X-ray photoelectron spectroscopy was performed using an X-ray photoelectron spectroscopy analyzer (manufactured by Fison Instruments, product name: S-PROBE TM2803).
[0098] [Average molecular weight] The average molecular weight of the polyamide was measured by size exclusion chromatography (SEC). A solution of lithium bromide in N,N-dimethylformamide with a lithium bromide concentration of 0.01M was used as the mobile phase, and the flow rate of the solution was set to 1.0 mL / min. Two columns (manufactured by Showa Denko K.K., product name: Shodex KD-806M) and a column oven (manufactured by GL Sciences K.K., product number: CO631A, set temperature: 40°C) were used.
[0099] [Thermogravimetric analysis (TGA)] Thermogravimetric analysis was performed using a differential thermal-thermogravimetric simultaneous analyzer (Hitachi High-Tech Science Corporation, model number: STA7200) by heating the sample in a nitrogen gas atmosphere (nitrogen gas flow rate: 250 mL / min) at a heating rate of 10°C / min in the temperature range from 25°C to 800°C.
[0100] [Compression test] A compression test was carried out at a compression speed of 1 mm / min using a universal material testing machine (manufactured by Instron, trade name: Series 3360 Load Frame).
[0101] [UV irradiation] Irradiation with ultraviolet light was carried out using an ultraviolet irradiation device (trade name: omniCure SERIES 1000 or 1500, manufactured by EXCELITAS TECHNOLOGIES (formerly LUMEN DYNAMICS)).
[0102] Preparation Example 1 (Preparation of diamine itaconate) Itaconic diamine has the following formula:
[0103] [ka]
[0104] More specifically, itaconic acid and cadaverine were weighed out in the air at room temperature (about 25°C) so as to have a molar ratio of 1:1. A solution in which 5.0 g of itaconic acid was dissolved in 10 mL of ethanol was mixed with a solution in which 3.9 g of cadaverine was dissolved in 10 mL of ethanol, and the resulting mixed solution was stirred for 12 hours to obtain a reaction mixture containing itaconate diamine.
[0105] The itaconate diamine produced was recovered from the reaction mixture by suction filtering the reaction mixture obtained above, and dried under reduced pressure at 50° C. for 48 hours.
[0106] The itaconate diamine obtained above was found to be a compound represented by formula (III) by the nuclear magnetic resonance (NMR) analysis shown in FIG. 1 This was confirmed by H-NMR spectroscopy. In FIG. 1, DMSO stands for dimethyl sulfoxide, and H2O stands for water.
[0107] Moreover, from the integrated areas of the peaks shown in FIG. 1, it was confirmed that in the itaconic acid diamine obtained above, itaconic acid and cadaverine reacted in a molar ratio of 1:1.
[0108] Production Examples 1 to 10 (Preparation of Polyamide) The polyamide has the following formula:
[0109] [ka]
[0110] (In the formula, n is a positive integer indicating the degree of polymerization.) More specifically, the diamine itaconate obtained above and sodium dihydrogen phosphate were mixed in a mass ratio of 1:0.01, and the mixture obtained was polymerized at 170°C in a nitrogen gas atmosphere. Various polyamides were obtained by changing the polymerization time as shown in Table 1. The polyamides obtained above had the formula:
[0111] [ka]
[0112] It was confirmed by nuclear magnetic resonance ( 1 The yield of the polyamide obtained in each production example is shown in Table 1. The name of the polyamide obtained in each production example is shown in the right column of Table 1.
[0113] [Table 1]
[0114] As a representative of the polyamides obtained above, the nuclear magnetic resonance (NMR) of polyamide I ( 1 The H-NMR spectrum is shown in Figure 2.
[0115] The nuclear magnetic resonance (NMR) of polyamide I shown in FIG. 1 The H-NMR spectrum showed peaks a, b, and c due to pyrrolidone rings, which were not present in itaconate diamine, confirming that a pyrrolidone ring was formed in polyamide I.
[0116] Polyamides other than polyamide I were also analyzed by nuclear magnetic resonance ( 1 H-NMR) of all polyamides was investigated. 1 In the 1 H-NMR spectrum, similarly to polyamide I, peaks due to the pyrrolidone ring appeared at 2.1 to 2.5 ppm and 3.0 to 3.3 ppm, confirming the formation of a pyrrolidone ring.
[0117] The molecular weights of the polyamide I and polyamide J obtained above were measured. As a result, the number average molecular weight of polyamide I was 2.59×10 3 The weight average molecular weight is 4.94 × 10 3 The number average molecular weight of polyamide J was 1.28 × 10 4 The weight average molecular weight is 2.43 × 10 4 It was.
[0118] The polyamide J obtained above was irradiated with ultraviolet light (wavelength: 250 to 450 nm) at an intensity of 150 mW / cm using an ultraviolet irradiator. 2 When the polyamide J was irradiated at 350 nm for 24 hours, the pyrrolidone ring of the polyamide J was opened, and it was confirmed that the polyamide J became hydrophilic in water at 25°C.
[0119] Polyamide J was immersed in a pepsin aqueous solution having a concentration of 1% by mass and a pH of 4.0 at room temperature and left for 6 weeks. The weight-average molecular weight of Polyamide J was then measured. The weight-average molecular weight of Polyamide J was 2.43 × 104 From 1.46 × 10 4 This confirmed that polyamide J is decomposed by pepsin, a digestive enzyme present in the human stomach, and its molecular weight is reduced.
[0120] Examples 1 to 5 (Preparation of Crosslinked Polyamide) Polyamide C, which represents the polyamides A to J obtained above, was used as a raw material for the crosslinked polyamide.
[0121] [ka]
[0122] (In the formula, n is a positive integer indicating the degree of polymerization.) More specifically, the polyamide C obtained above was heated in a nitrogen gas atmosphere at 210° C. for the time shown in Table 2 to obtain a polyamide having the formula (I) represented by R 1 A crosslinked polyamide was obtained in which the alkylene group had 5 carbon atoms.
[0123] When the water generated during heating of polyamide C was collected, the water was found to be basic using pH test paper, confirming that basic substances were vaporized when polyamide C was crosslinked. This suggests that a deammonia reaction of polyamide C occurred when polyamide C was crosslinked. The names of the crosslinked polyamides obtained in each example are shown in Table 2.
[0124] [Table 2]
[0125] Examples 6 to 8 (Preparation of Crosslinked Polyamide) The itaconate diamine obtained above was used as a raw material for the crosslinked polyamide. The itaconate diamine was heated in a nitrogen gas atmosphere at 210° C. for the time shown in Table 3 to directly convert itaconate diamine into the compound represented by R 1 In each example, a crosslinked polyamide was obtained in which the alkylene group had 5 carbon atoms. The names of the crosslinked polyamides obtained in each example are shown in Table 3.
[0126] [Table 3]
[0127] The crosslinked polyamides A to E and the crosslinked polyamides P to R obtained above each have a crosslinked structure represented by formula (I) as determined by infrared absorption spectroscopy, Fourier transform infrared spectroscopy (FT-IR), solid-state nuclear magnetic resonance ( 13 This was confirmed by C-NMR and X-ray photoelectron spectroscopy (XPS).
[0128] A comparison of the infrared absorption spectrum of Polyamide I by Fourier transform infrared spectroscopy (FT-IR) with that of Crosslinked Polyamide R by Fourier transform infrared spectroscopy (FT-IR) confirmed that there was no change in the peak positions of the infrared absorption spectra of both. This confirmed that no new functional groups were generated in Crosslinked Polyamide R, and no opening of the pyrrolidone ring occurred.
[0129] The results of X-ray photoelectron spectroscopy (XPS) of polyamide I and crosslinked polyamide R are shown in Fig. 3. In Fig. 3, (A) is a graph showing the XPS spectrum of polyamide I, and (B) is a graph showing the XPS spectrum of crosslinked polyamide R.
[0130] From the results shown in Figure 3, it can be seen that in Polyamide I, there is a peak derived from the CN bond of the amide at around 185 eV and a peak derived from the NH bond of the amino group at around 170 eV. In contrast, in Crosslinked Polyamide R, a peak derived from the CN bond of the amide is confirmed at around 185 eV, but there is no peak derived from the NH bond of the amino group at around 170 eV. From these results, it can be seen that in Crosslinked Polyamide R, the amino group disappears and a crosslinked structure is formed.
[0131] Next, the infrared absorption spectra of polyamide I, crosslinked polyamides A to E, and crosslinked polyamides P to R were examined by Fourier transform infrared spectroscopy (FT-IR). The results are shown in Figure 4. In Figure 4, the symbol X indicates the infrared absorption spectrum of polyamide I, and the symbols A to E and P to R indicate the infrared absorption spectra of crosslinked polyamides A to E and crosslinked polyamides P to R, respectively.
[0132] From the results shown in FIG. 4, no significant change in functional groups was observed when the crosslinked polyamide was prepared from polyamide I, which indicates that no new functional groups were generated and no pyrrolidone rings were opened in the crosslinked polyamide. 1 -R 1 It can be seen that a bridge is formed by the nitrogen atom present between the two.
[0133] Examples 9 to 16 (Production of aqueous gels) The crosslinked polyamide obtained in each Example was immersed in purified water at 25° C. for 24 hours to obtain an aqueous gel in which the crosslinked polyamide was saturated with water. Note that an aqueous gel saturated with water means an aqueous gel in which the water content hardly increases even if it is left for a longer period of time.
[0134] As the physical properties of the aqueous gel obtained above, the swelling rate with water and the water content were examined by the following measuring methods.
[0135] [Method of measuring swelling rate and water content] Mass of aqueous gel (W s ) was measured, and then the aqueous gel was freeze-dried to obtain the mass (W d ) was measured.
[0136] The mass (W s ) and the mass of the freeze-dried aqueous gel (W d ) to the formula: [Water swelling ratio (Q)] = [mass of aqueous gel (W s ) ÷ mass of freeze-dried aqueous gel (W d )] x 100 The swelling ratio (mass%) due to water was calculated based on the above. The results are shown in Table 4. The swelling ratio shown in Table 4 means the swelling ratio due to water.
[0137] The mass (W s ) and the mass of the freeze-dried aqueous gel (W d ) to the formula: [Moisture content] = [{mass of aqueous gel (W s )-Mass of freeze-dried aqueous gel (W d )} ÷ Mass of aqueous gel (W s )] x 100 The moisture content (mass%) was calculated based on the above. The results are shown in Table 4.
[0138] Next, as physical properties of the aqueous gel obtained above, the compressive elastic modulus and crosslink density were examined by the following measuring methods. The results are shown in Table 4.
[0139] [Method of measuring compressive elastic modulus and crosslink density] By carrying out a compression test on the aqueous gel obtained above, it was found that the composition had a viscosity of 100% by weight based on the formula: [Compressive modulus (E) = [Compressive stress (τ)] ÷ [L / L0 - (L / L0) -2 ] (In the formula, L is the thickness (mm) of the aqueous gel when compressed, and L0 is the thickness (mm) of the aqueous gel before compression.) The compressive elastic modulus (kPa) was calculated based on the above.
[0140] From the compressive elastic modulus (E) and the swelling rate due to water (Q) obtained above, the following formula is obtained: [Crosslink density (V e )]=[Compressive modulus (E)]÷[RTQ -1 / 3 ] (In the formula, R is the gas constant (8.31 m 2 kg s -2 ·K -1 mol -1 ), T is the absolute temperature at the time of measuring the compressive elastic modulus (E), and Q is the swelling rate due to water. Based on crosslink density (mg / cm 3 ) was sought.
[0141] For reference, we investigated the compressive elastic modulus of commercially available silicone worms, and the results are shown in the Reference Example column of Table 4.
[0142] [Table 4]
[0143] The results shown in Table 4 show that the crosslinked polyamide obtained in each Example has a superior compressive modulus compared to the conventional silicone worm.
[0144] It can be seen that the aqueous gels made of crosslinked polyamides P to R produced directly from itaconate diamine have a significantly higher crosslink density and superior compressive modulus compared to the aqueous gels made of crosslinked polyamides A to E produced by crosslinking polyamides.
[0145] In addition, the aqueous gels composed of crosslinked polyamides A to E and the aqueous gels composed of crosslinked polyamides P to R all have a swelling ratio in water of 210 to 300%, which indicates that they are easily swollen with water, and their water contents are in the range of 50 to 70%, which indicates that they have high water contents.
[0146] Next, the aqueous gel produced using the crosslinked polyamide P was immersed in water and exposed to ultraviolet light (wavelength: 250 to 450 nm) at room temperature using an ultraviolet irradiation device with an ultraviolet intensity of 150 mW / cm. 2 When the crosslinked polyamide P was irradiated at 400 K for 24 hours, it was confirmed that part of the crosslinked polyamide P had dissolved. This shows that crosslinked polyamide P is normally in the form of a gel, but that it gradually breaks down when irradiated with the ultraviolet rays contained in sunlight, demonstrating its excellent degradability in water. Furthermore, the decomposition products of the aqueous gel are polyamide or its raw materials, itaconic acid (salt) and diamine, and since all of these substances are water-soluble, they disappear in the natural environment and are highly safe for living organisms, demonstrating their environmental friendliness. [Industrial Applicability]
[0147] The aqueous gel of the present invention is expected to be used in a wide range of fields, such as a new artificial bait material to replace artificial baits such as silicone rubber worms, cell culture sheets, contact lenses, cosmetic packs, drug delivery materials for administering medicines into the body, artificial cartilage, artificial skin, artificial breasts, base materials for fragrances, electrolytes for lithium ion secondary batteries, vibration-proofing materials, and coating agents for various components that require hydrophilicity.
Claims
1. Formula (I): 【Chemistry 1】 (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. A crosslinked polyamide having a crosslinked structure represented by the following formula:
2. Crosslink density is 0.5 to 6 mg / cm 3 2. The crosslinked polyamide according to claim 1,
3. Itaconic acid or a salt thereof and a compound of formula (II): H 2 N-R 1 -NH 2 (II) (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. and a diamine represented by the formula:
4. Itaconic acid or a salt thereof and a compound of formula (II): H 2 N-R 1 -NH 2 (II) (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent. and heating said itaconate diamine to 200 to 250° C.
5. An aqueous gel comprising a crosslinked polyamide and water, the crosslinked polyamide having formula (I): 【Chemistry 2】 (In the formula, R 1 represents a direct bond or an alkylene group having 1 to 6 carbon atoms which may have a substituent.
2. An aqueous gel comprising a crosslinked polyamide having a crosslinked structure represented by the formula:
6. The aqueous gel according to claim 5, having a water content of 50 to 70% by mass.
7. A method for producing an aqueous gel, which comprises impregnating the crosslinked polyamide obtained according to claim 3 or 4 with water.
Citation Information
Patent Citations
Aqueous gelatinous hairdressing
JP1992356410A
Aqueous gel and method for producing the same
JP2003277637A
Cited By
Dynamic covalent bond in-situ self-repairing composite nanofiltration membrane based on temperature response and preparation method and application thereof
CN121490572A